The flight of the queen or the journey to the other side of the mirror: an interview with Tomás Eloy Martínez (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
In September 2002, we met with Tomás to talk about his new novel. We decided to do it formally; that's how we met in his office at Rutgers University. There, amidst photographs of his children and favorite authors, we began to review and talk about his new novel. (Interview)